(untitled) (Ustozlar uchun, 2026)
This article explores the significant role of reading books in enhancing language skills. It analyzes how reading contributes to vocabulary expansion, grammar development, and overall communication ability. The paper also highlights cognitive and psychological benefits associated with reading. Furthermore, it emphasizes the importance of consistent reading habits for language learners aiming for proficiency.